Intracellular pH Regulates Cancer and Stem Cell Behaviors: A Protein Dynamics Perspective - Liu, Yi; White, Katharine A.; Barber, Diane L. (Frontiers in Oncology, 2020)
The International Society of Cancer Metabolism (ISCaM) meeting on Cancer Metabolic Rewiring, held in Braga Portugal in October 2019, provided an outstanding forum for investigators to present current findings and views, and discuss ideas and future directions on fundamental biology as well as clinical translations. The first session on Cancer pH Dynamics was preceded by the opening keynote presentation from our group entitled Intracellular pH Regulation of Protein Dynamics: From Cancer to Stem Cell Behaviors. In this review we introduce a brief background on intracellular pH (pHi) dynamics, including how it is regulated as well as functional consequences, summarize key findings included in our presentation, and conclude with perspectives on how understanding the role of pHi dynamics in stem cells can be relevant for understanding how pHi dynamics enables cancer progression.